Sun protection and sunburn in children aged 1-10 years in germany: Prevalence and determinants - Görig, Tatiana; Södel, Corinna; Pfahlberg, Annette; Gefeller, Olaf; Breitbart, Eckhard; Diehl, Katharina (Children, 2021)
Seeking shade, the use of textile sun protection and sunscreen, and protecting one’s eyes by wearing sunglasses are recommended sun protection measures in children. We aimed to quantify the use of these measures as well as the prevalence of sunburn in children aged 1 to 10 years in Germany and to identify their determinants. Data collected via telephone interviews in a nationwide sample of 554 parents or caregivers in family were analyzed. Use of sunscreen was the most common measure applied (77.8%), while sunglasses were least frequently used (12.5%). The prevalence of sunburn during the past year was 21.8%, and it was positively associated with children’s age. The use of sun protection measures was significantly associated with the age and skin color of the child, while characteristics and tanning behaviors of the caregivers only played a minor role. The use of sun protection measures was higher when caregivers perceived themselves as a role model (Odds Ratio (OR) = 4.33, p < 0.001). Our nationwide data show that there remains a need for the improved use of sun protection measures, especially in children aged 7 to 10 years. In educational material, parents should be encouraged to become positive role models for their children regarding sun protection.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Children; Germany; Measures; Role model; Sun protection; Sunburn; Sunscreen